European Level Collective Bargaining: A New Phase? - Grahl, John; Teague, Paul (Relations industrielles / Industrial Relations, 1991)
After virtually two decades on the side lines, European level collective bargaining is back on the industrial relations agenda. To a large extent, the resurgence ofthis notion can be attributed to the impact of the EC's 1992 programme on European economic and political life. This article examines whether any significant changes or new developments will result from this increase in interest in European collective bargaining. The article suggests that there are two main dimensions to European level collective bargaining: the vertical dimension which covers attempts to get greater collaboration and dialogue between European trade unions and employers inside the institutional framework of the European Community; the horizontal dimension which includes developments at the enterprise and marketlevels aimed at promoting trade union /employer contact outside the confines of the nation state.